2016
DOI: 10.1080/09064702.2017.1313306
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of oestrous characteristics and conception in tie-stalled and loose-housed Swedish dairy cows

Abstract: The presence and importance of visual oestrous symptoms and the relation to conception, breed, housing system and milk yield were studied. Data were collected from a Swedish research herd during a 16-year period. Local, secondary and primary oestrous symptoms and an overall oestrus intensity score (OI) were studied. Decreasing trends in oestrous expression and conception rates (CR), and an increase in CR with more intensive oestrus, from 24% at OI score one (very week) to 54% at OI score five (very strong) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
1
5
1
Order By: Relevance
“…The lower total pregnancy loss for SR cows is in agreement with our earlier study where we found higher conception rates in SR cows than in SH cows based on transrectal pregnancy checks at approximately day 60 after AI [ 19 ]. Data on the effect of breed are very sparse in the literature.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The lower total pregnancy loss for SR cows is in agreement with our earlier study where we found higher conception rates in SR cows than in SH cows based on transrectal pregnancy checks at approximately day 60 after AI [ 19 ]. Data on the effect of breed are very sparse in the literature.…”
Section: Discussionsupporting
confidence: 91%
“…Early embryonic loss decreased with stronger oestrous expression, which was not surprising because our earlier study showed a positive association between oestrus intensity and conception rates [ 19 ]. These results are also in agreement with Pereira et al [ 28 ], who reported that a decrease in pregnancy losses (between 32 and 60 days of pregnancy) associates with cows expressing oestrus compared to no oestrus using protocols for timed insemination or timed embryo transfer.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…We did not find an association between any estrous characteristics and conception to AI. This is inconsistent with previous studies that report a positive association between estrous intensity or peak activity and conception rate (Madureira et al, 2015;Nyman et al, 2016). The lack of association in our study suggests estrous traits and conception traits could be selected separately.…”
Section: Conception and Estrous Characteristicscontrasting
confidence: 99%